Decrease of the DNA damage levels after sperm preparation by layering method - Mauri, A. L. [UNESP]; Baruffi, R. L R; Petersen, C. G. [UNESP]; Oliveira, J. B A; Vagnini, L.; Massaro, F. C.; Pontes, Anaglória [UNESP]; Franco Junior, Jose Gonçalves [UNESP] (My University, 2007)
The aim of this prospective study was to determine the DNA fragmentation levels before and after sperm preparation by layering method. A total of 78 patients submitted to assisted reproduction technology (ART) for infertility treatment were evaluated. Ejaculated spermatozoa were obtained by masturbation on the day of ART procedure. The evaluation of DNA fragmentation was performed in the fresh semen and after preparation by a layering method, respectively. After washing with PBS, the sperm pellets were smears and then processed for the terminal deoxyribonucleotidyl transferase (TdT)-mediated dUTP nick-end labelling (TUNEL) assay that was performed using a Cell Death Detection Kit with tetramethylrhodamine-labelled dUTP. For quantitative evaluation, 200 spermatozoa in randomly selected areas on microscope slides were evaluated and the percentage of TUNEL positive spermatozoa was determined. If ≥20% of selected sperm were TUNEL positive, the exam was considered abnormal. The mean percentage of DNA sperm fragmentation before sperm preparation was 17±8.3% and after 7.8±6.5% (p<0.0001). The exam was considered normal in 49 patients before preparation and in 73 patients after (p<0.0001). The sperm preparation with a layering method for the ART procedure is effective to select sperm with a significant decrease of the DNA damage.
Keywords: DNA fragmentation; Fertilizaç ão in vitro/ICSI; Layering method; Semen; TUNEL assay; tetramethylrhodamine; adult; controlled study; DNA damage; evaluation; human; infertility therapy; major clinical study; male; masturbation; microscope; nick end labeling; prospective study; quantitative analysis; smear; sperm; sperm preservation; spermatozoon; statistical significance